Estrutura genética de populações de Amphobotrys ricini, agente causal do mofo cinzento da mamoneira - Bezerra, Cintia de Sousa (2007)
The gray mold, causal organism Amphobotrys ricini, is one of the major diseases of castor bean. Difficulties in managing plant disease arises form the limited understanding of the genetic structure of A. ricini, their complexity and variability make it difficult to control. Genetic structure can be used to infer the relative impact of different forces that influence the evolution of pathogen populations, that allow to predict the potencial for pathogen populations to envolve in agricultural ecosystems. Growers protect their crop by applying fungicides, but there aren t fungicides to provide significant control of gray mold of castor bean. The objectives of this work were use RAPD to determine the genetic structure of A. ricini subpopulations in Paraíba and assay the sensitivity of A. ricini isolates to azoxystrobin and carbendazim. To determine the genetic structure of A. ricini subpopulations in Paraíba, 23 isolates were colleted from two different geographic location (subpopulation). These isolates were analysed by RAPD using 22 random decamer primers, purchased from OPERON, produced a total of 80 markers polimorphics. The resulting matrixes were analysed using PopGene version 1.32. Sensitivity to azoxystrobin and carbendazim of 30 isolates, colleted form Paraíba and Alagoas, was estimated based on spore germination and colony growth inhibition. The stock solutions were added toV8 medium after sterilization to produce final concentrations of 0, 0.01, 0.1, 1, 10, and 100 µg/ml of carbendazim and 0, 0.001, 0.01, 0.1, 1, and 10 µg/ml of azoxystrobin. All statistical analyses were performed using SAS to estimate the dose that inhibited fungal growth by 50% (ED50 values). The genetic diversity within subpopulations (Hs=0,271) accounted for 92% of the total genetic diversity (Ht=0,293), while genetic diversity between subpopulations (Gst = 0,075) represented only 7,5%. The estimated number of migrants per generation (NM ) was 6,15. Nei s average gene identity across 80 RAPD loci was 0,9468. Individual ED50 values, for the 30 isolates screened for their sensitivity to azoxystrobin, ranged From a maximum of 0,168 µg/ml to a minimum of 0,0036 µg/ml. The ED50 values for carbendazim varied within the range of 0,026 to 0,316 µg/ml